2013
DOI: 10.1073/pnas.1311135110
|View full text |Cite
|
Sign up to set email alerts
|

Self-contact elimination by membrane fusion

Abstract: Mutual, homophilic cell-cell adhesion between epithelial cells is required for proper maintenance of epithelial barrier function. Whereas opposing membranes from neighboring cells rapidly assemble junctional complexes, self-contacting membranes curiously do not, suggesting that cells have the ability to prevent the maturation of self-junctions. Using a self-contact-inducing microfabricated substrate, we show that self-contacts of normal epithelial cells are rapidly eliminated by membrane fusion between two opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Microfabrication of Pillar Array-The polydimethylsiloxane micropillar array was fabricated as previously described using standard soft lithography technique (4). The dimensions of individual pillars were 20 m in height and 5 m in diameter and arranged in a series of hexagons with an 18-m pitch along each hexagon side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microfabrication of Pillar Array-The polydimethylsiloxane micropillar array was fabricated as previously described using standard soft lithography technique (4). The dimensions of individual pillars were 20 m in height and 5 m in diameter and arranged in a series of hexagons with an 18-m pitch along each hexagon side.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of Self-contact-induced Membrane FusionThe method to quantify self-contact-induced membrane fusion has been described previously (4). Briefly, cells on self-contactinducing substrates were trypsinized to remove cell adhesion sites including self-junctions, then stained with phalloidin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent experiments with MDCK cells have shown that mammalian cells tend to eliminate self-contacts (Sumida and Yamada, 2013), a process that might be similar or identical to the EC self-fusion event occurring during pruning. E-cadherin is strictly required for self-contact elimination in MDCK cells, and further studies have shown that Rho GTPases and the downstream effectors Actin-related protein 2/3 (Arp2/3) complex and Myosin II induce membrane fusion at self-contacts of MDCK cells (Sumida and Yamada, 2015).…”
Section: Endothelial Cell Self-fusionmentioning
confidence: 99%
“…Wrapping and auto-fusion also generate some seamless tubes in the zebrafish vasculature [15] and in mammalian Madin-Darby Canine Kidney (MDCK) epithelial cells grown around silicone pegs [66], suggesting this mechanism may be widely used. MDCK auto-fusion requires cytoskeletal and trafficking regulators such as Rac, Rho, Cdc42 and the Arp2/3 complex [67], but the relevant fusogen is unknown.…”
Section: Mechanisms Of Seamless Tube Formationmentioning
confidence: 99%